Drilling Engineering : Advanced Applications and Technology - Miska, Stefan Z.; Mitchell, Robert F.; Ozbayoglu, Evren M. (McGraw-Hill's AccessEngineeringLibrary., 2022)
A guide for petroleum engineers covering the fundamentals through the latest advances in technology to drill both on and off shore wells as safely and economically as possible.